(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores the strategic role of radio as a vital tool for enhancing mass literacy in Nigeria, a country with persistent literacy disparities across its diverse regions. Nigeria’s literacy rate remains a significant developmental challenge, with rural and marginalized communities lagging behind urban centers. Historically, radio has been instrumental in Nigeria’s literacy campaigns due to its affordability, extensive coverage, and ability to broadcast in local languages, making it particularly effective in reaching remote populations where formal education infrastructure is limited. The evolution from simple broadcasts to interactive, community-based programs highlights radio’s adaptability to changing educational needs and technological advancements, sustaining its relevance over decades. However, systemic infrastructural issues such as unreliable power supply, limited access to radio devices, and socio-cultural barriers like gender norms and linguistic diversity have constrained its full potential. The study highlights the importance of community participation, culturally relevant content, and feedback mechanisms in increasing radio’s effectiveness for literacy promotion. Although past efforts have achieved notable successes, challenges related to funding, program design, and infrastructural deficits continue to hinder progress. This research emphasizes that leveraging radio’s full potential requires a comprehensive, participatory approach that incorporates technological innovations, local content, and policy support. The findings suggest that integrating radio with emerging technologies such as mobile phones, fostering community involvement, and addressing socio-cultural barriers can significantly enhance literacy outcomes. As Nigeria aims to meet global development goals like SDG 4, strengthening radio-based literacy initiatives could foster social inclusion, economic empowerment, and sustainable development. The study advocates for a strategic, multi-stakeholder effort to reimagine radio’s role in Nigeria’s literacy landscape, recognizing its capacity as a cost-effective, culturally sensitive, and scalable platform for achieving inclusive education and social transformation.